Brassinosteroids repress the seed maturation program during the seed-to-seedling transition. Issue 1 (23rd February 2021) - Ruan, Jiuxiao; Chen, Huhui; Zhu, Tao; Yu, Yaoguang; Lei, Yawen; Yuan, Liangbing; Liu, Jun; Wang, Zhi-Yong; Kuang, Jian-Fei; Lu, Wang-Jin; Huang, Shangzhi; Li, Chenlong
Abstract : Brassinosteroid plant hormones are involved in repressing the seed maturation program during the seed-to-seedling transition in Arabidopsis. Abstract: In flowering plants, repression of the seed maturation program is essential for the transition from the seed to the vegetative phase, but the underlying mechanisms remain poorly understood. The B3-domain protein VIVIPAROUS1/ABSCISIC ACID-INSENSITIVE3-LIKE 1 (VAL1) is involved in repressing the seed maturation program. Here we uncovered a molecular network triggered by the plant hormone brassinosteroid (BR) that inhibits the seed maturation program during the seed-to-seedling transition in Arabidopsis ( Arabidopsis thaliana ). val1-2 mutant seedlings treated with a BR biosynthesis inhibitor form embryonic structures, whereas BR signaling gain-of-function mutations rescue the embryonic structure trait. Furthermore, the BR-activated transcription factors BRI1-EMS-SUPPRESSOR 1 and BRASSINAZOLE-RESISTANT 1 bind directly to the promoter of AGAMOUS-LIKE15 ( AGL15 ), which encodes a transcription factor involved in activating the seed maturation program, and suppress its expression. Genetic analysis indicated that BR signaling is epistatic to AGL15 and represses the seed maturation program by downregulating AGL15 . Finally, we showed that the BR-mediated pathway functions synergistically with the VAL1/2-mediated pathway to ensure the full repression of the seed maturation program. Together, our work uncovered a mechanism underlying the suppression of the seed maturation program, shedding light on how BR promotes seedling growth.